Retinal Prosthesis A Clinical Guide to Successful Implementation (Essentials in Ophthalmology, 2018)
Intended as a useful and practical guide primarily oriented toward ophthalmic practitioners involved in retinal prosthesis implantation and post-operative visual rehabilitation, this book focuses on the Argus II Retinal Prosthesis and its revolutionary incorporation into the practice. The reader will get an update on patient selection, expected visual outcomes, surgical implantation techniques, and post-operative visual rehabilitation. Retinal Prosthesis - A Clinical Guide to Successful Implementation is written in a clear and concise manner and includes diagrams and high quality photographs to demonstrate best practices in surgical techniques and desired outcomes. Covering topics such as history of retinal prostheses, bioengineering considerations, clinical therapies, and other therapies and future directions, this book is written for practicing ophthalmologists, residents, and medical students interested in retinal implants.